2015
DOI: 10.1515/ijamh-2014-0021
|View full text |Cite
|
Sign up to set email alerts
|

Clinic attendance and health outcomes of youth with type 2 diabetes mellitus

Abstract: This study assessed whether clinic attendance was related to health outcomes for youth with type 2 diabetes mellitus (type 2 DM). Medical records of pediatric patients with type 2 DM were retrospectively reviewed. Clinic attendance was much more infrequent than recommended by physicians, and 42% of the sample withdrew from medical care. Patients who had a history of not showing during appointments had higher HbA1c levels than those who attended regularly scheduled visits; however, contrary to our hypotheses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
1
13
4
Order By: Relevance
“…Other studies that considered race among adult populations found similar significant associations . However, race was not significantly associated with attendance in paediatric populations attending diabetes clinics . This differs from our results, which showed an impact of black race on non‐attendance even after limiting to patients <18 years old and controlling for demographic, clinical and insurance characteristics.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Other studies that considered race among adult populations found similar significant associations . However, race was not significantly associated with attendance in paediatric populations attending diabetes clinics . This differs from our results, which showed an impact of black race on non‐attendance even after limiting to patients <18 years old and controlling for demographic, clinical and insurance characteristics.…”
Section: Discussioncontrasting
confidence: 97%
“…A US study among adults with HIV reported strikingly similar findings (aOR: 2.09; 95% CI: 1.10‐3.96) . However, in 2 separate cohorts of children attending diabetes clinics in the United States, clinic non‐attendance did not significantly vary by insurance type . It is challenging to directly compare our findings regarding insurance to those of studies conducted in countries with single payer health systems.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…It is a worry that 5% of cases did not attend any follow‐up after diagnosis, though significant loss to follow up has been described previously . Although a previous study has shown that clinic attendance and HbA1c are associated, we did not demonstrate this association in our study when we adjusted for other covariables. The challenge is engaging young people with T2DM in the diabetes clinical services and their management plan.…”
Section: Discussioncontrasting
confidence: 61%